PEER GROUP JUDGING: THE IMPLEMENTATION OF GROUP PIN-UP IN ARCHITECTURE DESIGN STUDIO - Megayanti, Trias; Aryanti, Tutin; Dewi, NItih Indra Komala (Journal of Architectural Research and Education, 2019)
The architecture design studio is a core course in architectural learning that trains students' abilities in the architectural design process. Unfortunately, students often fail to meet scheduled task targets, even though the time alloted is sufficient. This article examines the application of the group pin-up as a teaching method and its effectiveness in helping students meet deadlines for completing tasks in the Architecture Design III course, a studio attended by second year students. This study uses documents analysis (reviewing student design drawings to measure student achievement), and interviews (investigating changes in attitudes and perceptions of the students in pin-up group applications). We found that using the group pin-up strategy to impose an in-between deadline leads to improved discipline, better teamwork, and higher motivation due to competition in the group. This method is recommended in architectural design studios as a simulation practice for students before they move up and begin to work in the architecture profession.